Potential of Organic Amendments (AM fungi, PGPR, Vermicompost and Seaweeds) in Combating Salt Stress ... A Review - Reeta Kumari; Sonal Bhatnagar; Deepali; Neeti Mehla; Amit Vashistha (Plant Stress, 2022)
Climate change and agricultural practices such as the overuse of chemical fertilizers and pesticides have exacerbated the impact of abiotic pressures on crop productivity and degraded the ecosystem. Salinity is one of the major abiotic stress which affects agricultural yield. The increased salt concentration results in deteriorated soil aeration, soil compaction and affects various biochemical and physiological pathways. In response to salinity, plants show two phases, ion independent phase, and the ion-specific phase. In order to reduce soil salinization several conservation methods, such as appropriate irrigation, reduced inorganic fertilizer use, integrated agroforestry, tillage methods, and organic farming, can be used. To overcome or reduce the detrimental effect of soil salinity on plants alternative agricultural approach of organic amendments is a viable alternative to present farming techniques, which are unsustainable and have negative environmental repercussions. These contribute to a gradual release of nutrients and improved plant performance by providing a wide range of macro- and micronutrients. In the recent decade, a lot of studies have been conducted to highlight the importance of crop responses to abiotic stresses. To overcome this problem, organic amendments have been exploited to eliminate the negative impacts of several forms of abiotic stresses (drought, salinity, and metal) which is a major factor affecting a plant's yield. The present study is of great importance as in various areas of the world agriculture is increasingly threatened by salinity due to incorrect agricultural practices. Organic amendments applied separately or combined can help in preserving crop yields in an environmentally sustainable way.